1996
DOI: 10.1152/jappl.1996.81.1.194
|View full text |Cite
|
Sign up to set email alerts
|

Effects of spaceflight on bone mineralization in the rhesus monkey

Abstract: We combined dual-photon absorptiometry, iliac crest histomorphometry, and backscattered electrons analysis to characterize bone mineralization effects of a spaceflight on young monkeys. Two 4- to 5-kg male rhesus monkeys (Macaca mulatta) were flown during a 11.5-day spaceflight that took place onboard Cosmos 2229 biosatellite (Bion 10). Vivarium (n = 4) and Earth-based chair (n = 4) control situations were studied for comparison. Flight monkeys exhibited lower values of iliac cancellous bone volume, associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…Spaceflight decreases trabecular indices of bone formation in the iliac crest of monkeys [37,38], and human astronauts experience an imbalance in bone resorption and bone formation during spaceflight [2,39], which probably causes the cortical bone loss that is observed after 4-6 months in space [40,41]. Similarly, patients with acute spinal cord injury (< 6 months postinjury) experience increased bone resorption and increased urinary calcium excretion, which likely explains why spinal cord injury patients lose bone structural properties and demonstrate increased rates of bone fracture [12,16,42,43].…”
Section: Discussionmentioning
confidence: 99%
“…Spaceflight decreases trabecular indices of bone formation in the iliac crest of monkeys [37,38], and human astronauts experience an imbalance in bone resorption and bone formation during spaceflight [2,39], which probably causes the cortical bone loss that is observed after 4-6 months in space [40,41]. Similarly, patients with acute spinal cord injury (< 6 months postinjury) experience increased bone resorption and increased urinary calcium excretion, which likely explains why spinal cord injury patients lose bone structural properties and demonstrate increased rates of bone fracture [12,16,42,43].…”
Section: Discussionmentioning
confidence: 99%
“…Rahkmanov et al reported mineral loss in the proximal tibia after 2 weeks in space during an earlier mission [12]. In this mission, Zerath et al found less surface area involved and reduced mineralization rates in iliac crest biopsies, but at the organ level there was only a tendency for decreased mineral content during flight in two monkeys, and no changes in four chaired controls [22]. Whether these changes in the mineral content were associated with changes in bone biomechanics in the flight or control monkeys is not known.…”
Section: Introductionmentioning
confidence: 97%
“…Although each mission was limited to the participation of only two nonhuman primates in orbit for ϳ2 wk, the effects of microgravity on bone were evaluated by biopsies after the flight (38,39). As well, exercise activity, which may confound the interpretation of bone responses, was controlled during the flight.…”
mentioning
confidence: 99%